2022
DOI: 10.1021/acsami.1c21182
|View full text |Cite
|
Sign up to set email alerts
|

Surface Engineering and Trace Cobalt Doping Suppress Overall Li/Ni Mixing of Li-rich Mn-based Cathode Materials

Abstract: To supress Li/Ni mixing, the strategy of surface modification and Co doping is proposed. Doping trace Co can suppress Li/Ni mixing in the bulk phase of cathode particles, while the rock-salt shell of a cathode originally containing a large amount of Li/Ni mixed rows can be transformed into a cation-ordered spinel phase and a layered phase on the inside by means of surface engineering. Simultaneously, as a coating layer, the Li2MoO4 nanolayer forms on the surface. With the improved Li-ion diffusion, certain inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…From Figure 3b, LRO‐700 shows poor reversible capacity but outstanding stability due to the excessive electrochemical inactive MO‐type rock‐salt phase reduced capacity while protecting material interfaces. [ 54,55 ] In a word, LRO‐500 with controlled MO‐type phase content has a greater comprehensive performance among LRO‐400 (spinel‐only reconstructed surface) and LRO‐700 (excessive MO‐type rock‐salt reconstructed surface), indicating that the synergistic effect of MO‐type rock‐salt and spinel phase is the main reason for the improvement of LRO‐500. Compared to studies that only coated spinel phase [ 56–58 ] or rock‐salt phase, [ 59 ] this work showed much better cyclic performance.…”
Section: Resultsmentioning
confidence: 99%
“…From Figure 3b, LRO‐700 shows poor reversible capacity but outstanding stability due to the excessive electrochemical inactive MO‐type rock‐salt phase reduced capacity while protecting material interfaces. [ 54,55 ] In a word, LRO‐500 with controlled MO‐type phase content has a greater comprehensive performance among LRO‐400 (spinel‐only reconstructed surface) and LRO‐700 (excessive MO‐type rock‐salt reconstructed surface), indicating that the synergistic effect of MO‐type rock‐salt and spinel phase is the main reason for the improvement of LRO‐500. Compared to studies that only coated spinel phase [ 56–58 ] or rock‐salt phase, [ 59 ] this work showed much better cyclic performance.…”
Section: Resultsmentioning
confidence: 99%
“…The activation of the Li 2 MnO 3 phase is accompanied by the irreversible release of O 2 , which only occurs during the first charge–discharge cycle. Therefore, in the subsequent cycles, the oxidation peak near 4.7 V disappears [ 39 ], which is also the reason for the low initial Coulombic efficiency of Li-rich materials.…”
Section: Resultsmentioning
confidence: 99%
“…are drawing tremendous attention due to their low cost and high specific discharge capacity (>270 mAh g –1 ). , In electrochemistry, Li-rich Mn-based cathode materials possess higher electrochemical windows and charge compensation provided by transition metal cations and anions jointly at high charging potentials, being derived from the anionic redox reaction in the form of peroxide-like dimers (O 2– /O – ) and irreversible capacity loss in the form of surface lattice oxygen release. However, it is a double-edged sword. The irreversible oxygen release during the first cycle of activation triggers a detrimental structural transition that gradually diffuses from the particle surface into the bulk while it further deteriorates the reaction kinetics and structural stability, ultimately resulting in poor rate performance and a shortened cycle lifespan. , In the highly delithiated state, the phase transformation from a layered structure to a spinel-like structure of the cathode material caused by the irreversible oxygen loss at elevated temperature can also lead to a decline in thermal stability …”
Section: Introductionmentioning
confidence: 99%
“…The irreversible oxygen release during the first cycle of activation triggers a detrimental structural transition that gradually diffuses from the particle surface into the bulk while it further deteriorates the reaction kinetics and structural stability, ultimately resulting in poor rate performance and a shortened cycle lifespan. 9,10 In the highly delithiated state, the phase transformation from a layered structure to a spinel-like structure of the cathode material caused by the irreversible oxygen loss at elevated temperature can also lead to a decline in thermal stability. 11 To meet the challenges, numerous modification approaches such as surface coating, ion doping, and morphology controlling have been made in the past decades.…”
Section: Introductionmentioning
confidence: 99%